1999
DOI: 10.1017/s0007485399000486
|View full text |Cite
|
Sign up to set email alerts
|

Linear patterns of dispersal and build up of the introduced parasitoidMicroctonus hyperodae(Hymenoptera: Braconidae) in Canterbury, New Zealand

Abstract: The dispersal of Microctonus hyperodae Loan, an introduced parasitoid of the South American grassland pest Listronotus bonariensis Kuschel, was measured in Canterbury, New Zealand. Considering all directions, the mean annual dispersive increment was 1.9 ± 0.9 km year -1 as measured in the winters of 1993, 1994 and 1995. The parasitoid's ground distribution suggested that its movement was biased towards the south-west indicating probable wind-borne dispersal. The overall relatively low rate of dispersal was tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The dispersal rate of Irish M. aethiopoides appears to be more similar to Moroccan M. aethiopoides than M. hyperodae. Initial rates of spread of around 10 km year -1 were reported for M. aethiopoides in Australia (Aeschlimann 1983) while mean rate of M. hyperodae dispersal in the South Island (Goldson et al 1999) and the North Island (McNeill et al 2002b) was found to be under 2 km year -1 . Sitona spp.…”
Section: Discussionmentioning
confidence: 95%
“…The dispersal rate of Irish M. aethiopoides appears to be more similar to Moroccan M. aethiopoides than M. hyperodae. Initial rates of spread of around 10 km year -1 were reported for M. aethiopoides in Australia (Aeschlimann 1983) while mean rate of M. hyperodae dispersal in the South Island (Goldson et al 1999) and the North Island (McNeill et al 2002b) was found to be under 2 km year -1 . Sitona spp.…”
Section: Discussionmentioning
confidence: 95%
“…This experiment was established in September 1992, using weevils swept from a ryegrass/white clover paddock known to be parasitoid-free (Goldson et al, 1998a(Goldson et al, , 1999a and parasitoids reared from culture. The parasitoids used were all р 3 days old and had been provided with honeywater to increase their longevity as demonstrated by Hodgson et al (1993).…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…Population dynamics data were collected between 1992 and 1997 at the original 1991 M. hyperodae release site on the AgResearch farm at Lincoln (43°39ЈS, 172°28ЈE), 19 km south of Christchurch (Goldson et al, 1999a). The pasture consisted of a ryegrass (cv.…”
Section: Collection Of Population Dynamics Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, avoidance behavioral adaptations by adult L. bonariensis to presence of the parasitoid (Barratt et al 1996, Barker and Addison 1997, Gerard 2000 can lead to short eruptive phases of oviposition effort during periods when M. hyperodae are less abundant, and this may also signiÞcantly lessen the impact of the parasitoid (Barker and Addison 2006). Parasitism has been shown to severely suppress L. bonariensis ßight (Goldson et al 1999), which could lead to differential dispersal of a largely nonparasitized cohort of weevils.…”
mentioning
confidence: 99%